Risk of adverse perinatal outcomes among women with clinical and subclinical histopathological chorioamnionitis - Olguín-Ortega, Andrea; Figueroa-Damian, Ricardo; Palafox-Vargas, Martha Leticia; Reyes-Muñoz, Enrique (Frontiers in Medicine, 2024)
Introduction Histologic chorioamnionitis (HCA) is a placental inflammatory condition associated with adverse perinatal outcomes (APOs). This historical cohort study explores the risk of APOs in pregnant women with HCA and compares the impact of clinical chorioamnionitis (CCA) with subclinical chorioamnionitis (SCCA). Methodology Placentas were evaluated by a perinatal pathologist tand all women with HCA were included. Two groups were integrated: (1) women with clinical chorioamnionitis (CCA) and (2) women with subclinical chorioamnionitis (SCCA). Additionally, we conducted a secondary analysis to compare the prevalence of APOs among stage 1, 2 and 3 of HCA and the risk of APOs between grades 1 and 2 of HCA. The APOs analyzed were preterm birth, stillbirth, neonatal weight < 1,500 g, neonatal sepsis. Relative risk with 95% confidence interval was calculated. Results The study included 41 cases of CCA and 270 cases of SCCA. The mean gestational age at diagnosis and birth was 30.2 ± 5.4 weeks and 32.5 ± 5.1 weeks, for group 1 and 2, respectively. The study also found that women with HCA stage 3 and grade 2 had a higher prevalence and risk of adverse perinatal outcomes. Discussion The findings of this study suggest the importance of placental histological study to excluded SCCA, which represents a significant risk to both maternal and neonatal health, contributing to high morbidity and mortality.